Cryogel composites based on hyaluronic acid and halloysite nanotubes as scaffold for tissue engineering - Suner S.; Demirci S.; Yetiskin B.; Fakhrullin R.; Naumenko E.; Okay O.; Ayyala R.; Sahiner N. (Elsevier BV, 2019)
We present here preparation of mechanically strong and biocompatible cryogel composites based on hyaluronic acid (HA) and halloysite nanotubes (HNTs) of various compositions, and their applications as scaffold for different cell growing media. Uniaxial compression tests reveal that the incorporation of HNTs into HA cryogels leads to a ~2.5-fold increase in their Young moduli, e.g., from 38 ± 1 to 99 ± 4 kPa at a HA:HNTs weight ratio of 1:2. Although HA:HNTs based cryogels were found to be blood compatible with 1.37 ± 0.11% hemolysis ratio at a HA:HNTs weight ratio of 1:2, they trigger thrombogenic activity with a blood clotting index of 17.3 ± 4.8. Remarkably, HA:HNTs cryogel composites were found to be excellent scaffold materials in the proliferation of rat mesenchymal stem cells (MSC), human cervical carcinoma cells (HeLa), and human colon cancer cells (HCT116). The cell studies revealed that an increased amount of HNT embedding into HA cryogels leads to an increase of MSC proliferation.
Keywords: Nanotubes; Tissue Engineering; Tissue Scaffolds; Halloysite nanotubes; Hyaluronic acid; Spectrum Analysis; Biocompatible Materials; Hemolysis; Materials Testing; Thermogravimetry; Animals; Clay; Humans; Tissue engineering; Blood compatibility; Composite cryogels; Hyaluronic Acid; Cells, Cultured; Cryogels